Documents and the history of the early Islamic world - Schubert, Alexander T.; Sijpesteijn, Petra. (Islamic History and Civilization, 2015)
Historians have long lamented the lack of contemporary documentary sources for the Islamic middle ages and the inhibiting effect this has had on our understanding of this critically important period. Although the field is richly served by surviving evidence, much of it is hard to locate, difficult to access, and philologically intractable. Presenting a mixture of historical studies and new editions of Greek, Arabic and Coptic material from the seventh to the fifteenth century C.E. from Egypt and Palestine, Documents and the History of the Early Islamic World explores the untapped wealth of documentary sources available in collections around the world and shows how this exciting material can be used for historical analysis. Contributors include: Hugh Kennedy, Anne Regourd, Jairus Banaji, Alain Delattre, Shaun O'Sullivan, Anna Selander, Frédéric Bauden, Mostafa El-Abbadi, Rachel Stroumsa, Sebastian Richter, Tascha Vorderstrasse, Matt Malczycki, R.G. Khoury, Nicole Hansen, and Alia Hanafi. For more titles about Papyrology, please click here .